Responses of soil fertility indicators and fungi community diversity to fertilization strategies in legume-grass mixtures - Chen, Jingru; Chen, Xiaoshan; Nan, Li li (Frontiers in Plant Science, 2025)
IntroductionAlfalfa-grass binary mixtures outperformed monocultures in nutrient use, soil nutrient content, and biomass yield. Nonetheless, the impact of fertilization strategies on fungal community composition and ecological functions in legume-Grass mixtures remains under-researched. This study aimed to explore the effects of different fertilization strategies on soil fungal community distribution and soil environmental characteristics.MethodsA field experiment in Gansu, China, has been conducted to explore the effects of five different fertilization strategies—no fertilization (CK), three partial fertilization methods (+PK, +NK, +NP), and balanced fertilization (+NPK)—on fungal population richness, community composition, and soil environmental drivers. Rhizosphere soils from the five treatments were sampled and investigated using high-throughput ITS sequencing.ResultsCompared to CK, +NPK led to higher soil capabilities (P< 0.05), soil organic matter (SOM), available nitrogen (AN), available phosphorus (AP), and available potassium (AK) increased by an average of 29.7 %, 42.3 %, 101.2 %, and 24.3 %, respectively; alkaline phosphatase (APA), catalase (CAT), and sucrase (SA) increased by an average of 56.6 %, 31.8 %, and 46.7 %, respectively; soil microbial biomass carbon (SMBC), soil microbial biomass nitrogen (SMBN), and soil microbial biomass phosphorus (SMBP) increased by an average of 64.8 %, 65.1 %, and 60.4 %, respectively. The dominant fungi in the rhizosphere soil were Mortierellomycota and Ascomycota, accounting for 82.2%-92.3%. The fungal species richness was the highest in the +PK treatment. From the NMDS and RDA analysis, it can be discerned that SA, AK, and CAT were the key environmental factors influencing the structure of the inter-root soil fungal community in alfalfa; CAT and SOM were the key environmental factors influencing the structure of the inter-root soil fungal community in awnless brome.DiscussionOur findings investigated the optimal fertilizer strategy for legume-Grass mixtures. Results provided a technical basis for scientific fertilizer application and development of local mixed grassland ecosystems.